FOSTERING CURIOSITY IN SCIENCE THROUGH OPA OLENG: A WORD PUZZLE-BASED OUTDOOR LEARNING FOR JUNIOR HIGH SCHOOL - Nisa, Wilda Muhimmatun; Tyas, Rizki Arumning (Universitas Tanjungpura, 2025)
This study aims to determine the effect of OPA OLENG (Word Puzzle Outdoor Learning) learning on increasing the curiosity of junior high school students. The method used in this study is a pre-experimental design that does not include a control group, with a one group pretest posttest design model. The sample in this study was one class VIIIE SMPN 2 Genteng for the academic year 2021/2022 with 30 students using simple random sampling technique. The data collection technique used is a curiosity indicator questionnaire which is contained in 26 questions. The data analysis technique used is standard gain value analysis and descriptive analysis by describing using the percentage formula. Based on the results of the research data analysis and discussion, it can be concluded that the students' curiosity after the OPA OLENG learning was applied increased with an N-Gain score of 0.51 in the medium category. The average percentage value of the curiosity descriptive analysis increased from 72.55% with moderate criteria to 88.70% with high criteria. Based on the research findings, it can be concluded that the implementation of OPA OLENG (Word Puzzle Outdoor Learning) significantly enhances the curiosity of junior high school students in science learning. This study highlights the potential of outdoor, game-based learning like OPA OLENG to foster an engaging and curiosity-driven learning environment. Such approaches can be particularly valuable in science education, where promoting active exploration and interest is crucial. Schools and educators may consider incorporating outdoor word puzzle activities to support curiosity and enthusiasm for learning among students. Future research could explore variations of this approach with different age groups and subject areas to further validate its effectiveness.